Study Of The Development Of The Functional Program In Light Of Information Technology A Comparative Study Between Modern International Libraries - غانم, تألق (Latakia University Journal -Engineering Sciences Series, 2025)
Recently, information and communication systems have developed significantly, as the use of technology in our current era has come to mean scientific knowledge in practical application. It was necessary for architecture to be compatible with the technological context, starting from the design production process stage until the final product. The governing framework for the success of any architectural work is the formulation of a functional program with the design standards and foundations specific to the building’s function. Since the beginning of the second half of the twentieth century until the present time, there have been tremendous developments in the field of technology and the field of information technology in architecture in particular. Since that time, we find that most of the functional functions and tasks have been replaced by a specific technological mechanism. Consequently, the globally approved functional architectural programs no longer achieve what is required of them and do not keep pace with future aspirations. Therefore, evaluating the functional architectural program in light of the development of information technology that we are witnessing and re-studying it is a helpful tool to increase the efficiency of the architectural product. The term information technology in architecture has spread widely recently, as the functional program can be considered appropriate when it adapts to the conditions of the era and the requirements of users and changes itself accordingly. Hence, the study was directed to search for the study of the development of the functional program in light of information technology on the functional programs of architectural projects in general and libraries in particular by studying regional and international models of public library buildings built since the beginning of the emergence of information technology in architecture and the beginning of reliance on it to perform some of the functions assigned to users.